Assessment of biology students’ knowledge about the fauna and flora of the Campos Gerais - Macedo, Ana Lucia de Souza; Alves, Gustavo Henrique Zaia (Acta Scientiarum. Biological Sciences, 2025)
Brazil stands out globally for its rich biodiversity, presenting a vast field of study. Despite this natural wealth, the population exhibits limited knowledge about it. This study was conducted at the Universidade Estadual de Ponta Grossa with Biology students to assess their perception of the native fauna and flora of Campos Gerais, Paraná. Data were collected in 2023 through questionnaires with 36 participants, including students at the beginning and end of their course. The results showed that, although students at the end of the course had slightly higher recognition of species, the difference was not statistically significant. Interestingly, the identification of exotic species surpassed that of many native species, including endangered species such as the giant anteater. We conclude that a knowledge gap exists regarding native species among future biologists and educators, underscoring the need to integrate place-based teaching approaches and revise educational materials.